Properties of Whey-Protein-Coated Films and Laminates as Novel Recyclable Food Packaging Materials with Excellent Barrier Properties - Markus Schmid; Kerstin Dallmann; Elodie Bugnicourt; Dario Cordoni; Florian Wild; Andrea Lazzeri; Klaus Noller (International Journal of Polymer Science)
In case of food packaging applications, high oxygen and water vapour barriers are the prerequisite conditions for preserving the quality of the products throughout their whole lifecycle. Currently available polymers and/or biopolymer films are mostly used in combination with barrier materials derived from oil based plastics or aluminium to enhance their low barrier properties. In order to replace these non-renewable materials, current research efforts are focused on the development of sustainable coatings, while maintaining the functional properties of the resulting packaging materials. This article provides an introduction to food packaging requirements, highlights prior art on the use of whey-based coatings for their barriers properties, and describes the key properties of an innovative packaging multilayer material that includes a whey-based layer. The developed whey protein formulations had excellent barrier properties almost comparable to the ethylene vinyl alcohol copolymers (EVOH) barrier layer conventionally used in food packaging composites, with an oxygen barrier (OTR) of <2 [cm³(STP)/(m²d bar)] when normalized to a thickness of 100 μm. Further requirements of the barrier layer are good adhesion to the substrate and sufficient flexibility to withstand mechanical load while preventing delamination and/or brittle fracture. Whey-protein-based coatings have successfully met these functional and mechanical requirements.